Performance analysis of solar water heater combined with heat pump using refrigerant mixture - Atipoang Nuntaphan (2018)
In the research presented in this paper the thermal performance of a solar water heater combined with a heat pump is studied. A solar collector was modified from corrugated metal roofing with a copper tube attached beneath. The performance of the solar water heater was tested, and models for the collector efficiency and storage tank were developed and used for the evaluation of their performance when combined with a heat pump system. The performance of the combined solar water heater and heat pump was investigated using a simulation program. In this analysis, a model for a heat pump using the refrigerant mixture R22/R124/R152a was selected. From the simulation program, the results show that the highest performance occurred at a mass fraction of R22 = 20%, R124 = 57% and R152a = 23%, a compressor speed of 20 rps, and mass flow rate of refrigerant at 0.01 kg/s. The coefficient of performance (COP) of this system is between 2.5 and 5.0. Moreover, economic analysis shows that the suitable mass of hot water in the storage tank is 400 kg and that the payback period for this system is 2.3 years. © 2008 Elsevier Ltd. All rights reserved.